Filaments in the southern giant lobe of Centaurus A: Constraints on nature and origin from modelling and GMRT observations - Wykes, S.; Intema, Hubertus; Hardcastle, M.; Achterberg, A.; Jones, T.; Jerjen, H.; Orrú, E.; Lazarian, A.; Shimwell, T.; Wise, M.; Kronberg, P. (Oxford University Press, 2014)
We present results from imaging of the radio filaments in the southern giant lobe of CentaurusA using data from Giant Metrewave Radio Telescope observations at 325 and 235 MHz, and outcomes from filament modelling. The observations reveal a rich filamentary structure, largely matching the morphology at 1.4 GHz. We find no clear connection of the filaments to the jet. We seek to constrain the nature and origin of the vertex and vortex filaments associated with the lobe and their role in high-energy particle acceleration. We deduce that these filaments are at most mildly overpressuredwith respect to the global lobe plasma showing no evidence of largescale efficient Fermi I-type particle acceleration, and persist for ~2-3 Myr. We demonstrate that the dwarf galaxy KK 196 (AM 1318-444) cannot account for the features, and that surface plasma instabilities, the internal sausage mode and radiative instabilities are highly unlikely. An internal tearing instability and the kink mode are allowed within the observational and growth time constraints and could develop in parallel on different physical scales. We interpret the origin of the vertex and vortex filaments in terms of weak shocks from transonic magnetohydrodynamical turbulence or from a moderately recent jet activity of the parent AGN, or an interplay of both. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.